Quality of life in neurofibromatosis 1: development and validation of a tool dedicated to cutaneous neurofibromas in adults. (28th April 2022) - Fertitta, L.; Bergqvist, C.; Armand, M.L.; Moryousef, S.; Ferkal, S.; Jannic, A.; Ravaud, P.; Tran, V.T.; Ezzedine, K.; Wolkenstein, P.
Abstract: Background: Cutaneous neurofibromas (cNF), present in 95% of individuals with neurofibromatosis 1 (NF1), are considered as one of the greatest medical burden because of physical disfigurement. No specific score evaluates their impact on quality of life (QoL). Objective: To develop a specific score assessing cNF‐related QoL. Methods: Through a multidisciplinary workshop including 10 patients, 3 expert‐in‐NF1 physicians, 3 health care workers (nurses and psychologist) and 1 methodologist, the French version of the Skindex‐16 was modified by adding 3 items. The new cNF‐Skindex was validated among patients with NF1 recruited in the ComPaRe online cohort, in France ( N  = 284). Construct validity was assessed by comparing it with the EQ‐5D‐5L, its visual analogue scale and the MYMOP2 and by assessing its association with patients' characteristics. Reliability was assessed by a test–retest. An English version of the tool was developed using a back‐forward translation. Results: A total of 228 individuals with NF1, with cNF answered the 19‐item questionnaire. These items fitted into 3 domains: emotions, symptoms, functioning. One was dropped during analysis because >90% responders were not concerned. The cNF‐Skindex significantly correlated with the EQ‐5D‐5L ( N  = 193) and MYMOP2 ( N  = 210) indicating good external validity: rs 0.38 ( P  < 0.001), and 0.58 ( P  < 0.001), respectively. Having >50 cNF was the only independent variable associated with the total score cNF‐Skindex (β = 15.88, 95%CI 6.96–24.81, P  = 0.001), and with the 3 sub‐scores: 'functioning' (β = 2.65, 95%CI 0.71–4.59, P  = 0.008), 'emotions' (β = 17.03, 95%CI 4.11–29.96, P  = 0.010) and 'symptoms' (β = 3.90, 95%CI 1.95–5.85, P  < 0.001). Test–retest reliability ( N  = 133) found an ICC at 0.96 demonstrating good reproducibility. Conclusion: The cNF‐Skindex demonstrated excellent psychometric properties. The global and sub‐scores were increased with higher number of cNF arguing for its use in further trials aiming to reduce their number or prevent their development. Cross‐cultural validation and evaluation of its responsiveness are the next steps.